PERBANDINGAN PENGARUH PENEMPATAN ARRESTER SEBELUM DAN SESUDAH FCO SEBAGAI PENGAMAN TRANSFORMATOR 3 PHASA TERHADAP GANGGUAN SURJA PETIR DI PENYULANG PANDEAN LAMPER 5 RAYON SEMARANG TIMUR - Wardana, Azis Nurrochma; Subari, Arkhan (Vocational School Diponegoro University, 2014)
Azis Nurrochma Wardana, Arkhan Subari, in paper comparison of the effect of placement arrester before and after FCO as safety of 3 phase transformator from interruption of lightning at Pandean Lamper 5 Feeder, East Semarang explain that problem of the studied is location of arrester at distribution which have is same function and target but owning location of different arrester. Location of arresterÂ relate to wiring of arrester with transformer and fuse Cut Out (FCO) owning target to give protection at transformer of over voltage. In the last location of this arrester require to study again about its efficacy of its at transformer. Efficacy of pr otection at such transformer is efficacy of passed to protection is transformer by minimizing over voltage that happened at the transformer so that equipments and transformer which its of him do not experience of damage. By considering factor influencing the level of voltage of surge and current of surge that happened at each system, like wiring of arrester, length of wire, apart arrester which is utilized in system location of arrester, steepness of wave come, speed creep waving surge, and Basic InsulationLevel (BIL) equipments, so that is in the final got one of location of correct arrester as 20 kV distribution transformer protection. Keywords: Arrester, Distribution Transformer, Fuse Cut Out, Lightning Surge